2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9030049
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative behavior and robustness of dendritic trafficking

Abstract: The paper studies homeostatic ion channel trafficking in neurons. We derive a nonlinear closed-loop model that captures active transport with degradation, channel insertion, average membrane potential activity, and integral control. We study the model via dominance theory and differential dissipativity to show when steady regulation gives way to pathological oscillations. We provide quantitative results on the robustness of the closed loop behavior to static and dynamic uncertainties, which allows us to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the exact nature of the feedback signal is unknown. We therefore used the averaged delivery rate over all , which amounts to simple proteostasis and is a realistic feedback signal in a neuron ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact nature of the feedback signal is unknown. We therefore used the averaged delivery rate over all , which amounts to simple proteostasis and is a realistic feedback signal in a neuron ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Under such assumptions the analysis we developed here could provide a starting point for a model of local, distributed regulation. Further work, including our own ongoing work 73 , can connect such local regulation to the global regulation at the level an entire, spatially extended cell.…”
Section: Consequences Of Modeling Calcium Concentration Using a Singlmentioning
confidence: 99%
“…The second observation, derived from simulations, is that growth adaptation may compensate for pathological oscillations, enabling more aggressive synaptic scaling. Aggressive feedback gains k u may lead to pathological oscillations in synaptic scaling [9], as shown in Figure 6(a). However, these oscillations are dampened through growth adaptation, as shown in Figure 6(b), reaching the desired set-point.…”
Section: Homeostasis By Fast Synaptic Scaling and Slow Growth Adaptationmentioning
confidence: 99%
“…The synthesis process of ion channels and receptor proteins depends on a feedback signals, including calcium influx [6], [7]. Previous work showed that transport processes suffer from severe delays [8], and can pose a potential source of instability in the presence of cellular feedback control [9].…”
Section: Introductionmentioning
confidence: 99%